A hollow fiber gas separation membrane
By adopting the preparation method of hollow fiber gas separation membrane and using the mixing and processing technology of specific materials, the existing CO2/CH4 separation membrane has been solved, and more efficient CO2 separation and stronger membrane strength are achieved, which is suitable for separation of CO2/CH4 systems.
Patent Information
- Application Number
- CN202411890475.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The separation performance of the existing CO2/CH4 separation membrane is not ideal, and the membrane strength is insufficient and the service life is not long.
Using the preparation method of hollow fiber gas separation membrane, by mixing glyceryl monoacetate and isobutyl acetate with polyether sulfone, sulfonated polyether ether ketone and polyvinylpyrrolidone-k60 and other materials, after a series of stirring, ball milling, cooling and heat treatment, a cast film liquid is formed, and spinning in glycerol through a spinneret, and finally cleaning and heat treatment is carried out in ethylene glycol and dimethyl silicone oil to obtain a hollow fiber gas separation membrane.
It significantly improves the CO2 separation performance and membrane strength of the CO2/CH4 separation membrane, is suitable for the separation of CO2/CH4 systems, and has high preparation process efficiency, which is suitable for large-scale production.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of membrane materials, in particular to a hollow fiber gas separation membrane. Background Art
[0002] Biogas (BNG) is an emerging renewable clean energy source. The core of biogas production is the removal of carbon dioxide from biogas. Currently, the main methods for separating CO2 / CH4 include adsorption separation, cryogenic separation, and membrane separation. Adsorption separation utilizes the differences in adsorption capacity of adsorbents for CO2 and CH4 to achieve separation. Commonly used adsorbents include zeolites, activated carbon, and metal-organic frameworks (MOFs). This method requires relatively simple equipment and offers flexible operation, making it suitable for small- to medium-scale applications. However, its disadvantages are the high energy consumption for adsorbent regeneration and the need for regular replacement. Cryogenic separation achieves separation by cooling the mixed gas to extremely low temperatures, causing the CO2 to condense at low temperatures. This method is suitable for applications requiring high purity, but it consumes more energy and requires significant equipment investment.
[0003] Membrane separation technology utilizes the differences in permeation rates of different gas molecules through membrane materials to achieve separation. CO2 / CH4 separation membrane technology is considered one of the most promising technologies in biogas purification. The selection and design of membrane materials significantly influence separation efficiency. Commonly used membrane materials include polymer membranes and inorganic membranes. The membrane biogas purification process includes gas purification, compression, cooling, and drying, ultimately achieving high-purity biogas. In recent years, researchers have used polyether copolyamide (Pebax) as the separation layer membrane material and prepared composite gas separation membranes by a dip-coating method. They investigated the permeation and separation performance of Pebax composite membranes for pure gases such as CH4, CO2, and H2S, as well as CO2 / CH4 mixtures across a range of concentrations. The technical feasibility of Pebax gas separation membranes for biogas purification was simulated using a spiral wound membrane separator cross-flow model. The results showed that Pebax membranes exhibited a certain CO2 permeation flux and CO2 / CH4 separation coefficient. In addition, researchers have synthesized polyethersulfone (PES) using tetramethylbiphenol, dichlorodiphenyl sulfone, and difluorobenzophenone as monomers through polycondensation, and then prepared amino-functionalized PES gas separation membranes through bromination and amination, which has improved separation performance to a certain extent. However, the separation performance of these membranes still needs to be improved, and they generally suffer from problems such as low membrane strength and short service life. Summary of the Invention
[0004] The technical problem to be solved by the present invention is: how to develop a gas separation membrane with better CO2 / CH4 separation performance and higher strength.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0006] A hollow fiber gas separation membrane is prepared by the following method:
[0007] 1) Add monoacetin and isobutyl acetate to a stirring kettle and stir evenly at 40-60°C. Add polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-K60 and stir at 80-90°C for 1-2 hours. Then cool to 50-60°C, add polyvinyl alcohol, cool to 30-40°C and keep warm. Then add zirconium oxide powder and ball mill. Then add polyacrylamide and ball mill. Stir under negative pressure for 8-12 hours. Transfer to a spinning kettle and let it stand for degassing to obtain a casting solution.
[0008] 2) Diethylene glycol and propylene carbonate are mixed to obtain a core liquid. The casting liquid is degassed and then added to a spinneret. The core liquid is injected into the inner tube of the spinneret. The casting liquid is extruded into 90% glycerol at 5°C to solidify, and then washed in an ethylene glycol environment at 50°C. It is then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane.
[0009] 3) The hollow fiber membrane was cleaned with deionized water, rinsed in a methanol environment at 55° C., and then washed with deionized water and dried to obtain the hollow fiber gas separation membrane.
[0010] Preferably, in step 1), the mass ratio of monoacetin to isobutyl acetate is 1:2 to 1:3.5.
[0011] Preferably, in step 1), the molar ratio of polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60 is 1:4:2.5.
[0012] Preferably, in step 1), the amount of zirconium oxide powder added is 1 / 8 to 1 / 15 of the mass of polyethersulfone, the rotation speed of the first ball milling is 300 rpm, and the rotation speed of the second ball milling is 550 rpm.
[0013] Preferably, the negative pressure state in step 1) is 0.2-0.35 atmospheres, the stirring time under the negative pressure state is 5-8 hours, and the temperature is 25-35°C.
[0014] Preferably, during the static degassing process in step 1), the system is placed in an ultrasonic oscillation environment, the static degassing time is 3-6 hours, and the temperature is 25-35°C.
[0015] Preferably, the ratio of polyethersulfone, sulfonated polyetheretherketone, polyvinylpyrrolidone-k60, polyvinyl alcohol, zirconium oxide powder, polyacrylamide, glycerol monoacetate, isobutyl acetate, glycol, and propylene carbonate is 10g: 7.8g: 4.2g: 5.5g: 1.35g: 3.13g: 20mL: 13mL: 17mL: 5mL.
[0016] Preferably, in step 2), the water pressure entering the inner diameter of the spinning head is 1.8 bar and the water flow rate is 140 mL / min.
[0017] Preferably, in step 2), the hollow fiber membrane embryo is kept in 90% glycerol at 5° C. for no less than 40 minutes.
[0018] Preferably, the drying in step 3) is vacuum drying at a temperature of 40-50°C.
[0019] Preferably, in step 3), after the drying step is completed, the hollow fiber gas separation membrane is kept in a nitrogen and oxygen environment with a volume ratio of 1:1 for 20 to 30 minutes.
[0020] The present invention provides a hollow fiber gas separation membrane. The technical solution first constructs a mixed solvent with monoacetin and isobutyl acetate, mixes it with polyethersulfone, sulfonated polyetheretherketone and a porogen under medium temperature conditions, and then cools it step by step and adds polyvinyl alcohol and zirconium oxide powder in sequence. After one ball milling, polyacrylamide is added, and then ball milled again to obtain a casting liquid system, which is then allowed to stand for degassing and used for standby use; the core liquid uses diethylene glycol and propylene carbonate, and a hollow fiber membrane embryo is extruded using a hollow fiber membrane spinning machine, which is directly put into a 90% glycerol coagulation bath to cause phase separation and solidification, and then is washed and heat treated at medium temperature to obtain a hollow fiber gas separation membrane. The present invention has excellent carbon dioxide separation performance, and the membrane strength is significantly improved, and is particularly suitable for the separation of CO2 / CH4 systems. In addition, the preparation process of the present invention has high efficiency and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the hollow fiber gas separation membrane of the present invention.
[0022] Figure 2 yes Figure 1 A partial enlarged view of . DETAILED DESCRIPTION
[0023] The following is a detailed description of specific embodiments of the present invention. To avoid excessive unnecessary detail, well-known structures or functions will not be described in detail in the following examples. Approximate language used in the following examples can be used for quantitative expression to indicate that a certain amount of variation is allowed without changing the basic function. Unless otherwise defined, technical and scientific terms used in the following examples have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0024] Example 1
[0025] A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 40°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-K60, stirring at 80°C for 1 hour, then cooling to 50°C, adding polyvinyl alcohol, cooling to 30°C and keeping warm, then adding zirconium oxide powder, ball milling, then adding polyacrylamide, ball milling, stirring under negative pressure for 8 hours, transferring to a spinning kettle and letting it stand for degassing to obtain a membrane casting solution; 2) adding diglycerol Alcohol and propylene carbonate are mixed to obtain a core liquid. The casting liquid is degassed and then added to a spinneret. The core liquid is injected into the inner tube of the spinneret. The casting liquid is extruded into 90% glycerol at 5°C to solidify. The liquid is then washed in an ethylene glycol environment at 50°C and heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane. 3) The hollow fiber membrane is washed with deionized water, rinsed in a methanol environment at 55°C, and then washed with deionized water and dried to obtain the hollow fiber gas separation membrane. The resulting hollow fiber gas separation membrane has a breaking strength of 72 MPa. Its performance is tested using a mixture of CO2 and CH4 (volume ratio of 25:75). When the feed gas pressure is 0.13 MPa, the CO2 permeation rate is 2100×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 256.
[0026] Example 2
[0027] A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring uniformly at 60°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-K60, stirring at 90°C for 2 hours, then cooling to 60°C, adding polyvinyl alcohol, cooling to 40°C and keeping warm, then adding zirconium oxide powder, ball milling, then adding polyacrylamide, ball milling, stirring under negative pressure for 12 hours, transferring to a spinning kettle and standing for degassing to obtain a membrane casting solution; 2) adding diglycerol Alcohol and propylene carbonate are mixed to obtain a core liquid. The casting liquid is degassed and then added to a spinneret. The core liquid is injected into the inner tube of the spinneret. The casting liquid is extruded into 90% glycerol at 5°C to solidify. The membrane is then cleaned in an ethylene glycol environment at 50°C and heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane. 3) The hollow fiber membrane is cleaned with deionized water, rinsed in a methanol environment at 55°C, and then washed with deionized water and dried to obtain the hollow fiber gas separation membrane. The resulting hollow fiber gas separation membrane has a breaking strength of 77 MPa. Its performance is tested using a mixture of CO2 and CH4 (30:70 by volume). When the feed gas pressure is 0.15 MPa, the CO2 permeation rate is 2400×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 280.
[0028] Example 3
[0029] A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-K60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C and keeping warm, then adding zirconium oxide powder, ball milling, then adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle and standing for degassing to obtain a membrane casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid. The casting liquid is degassed and then added to a spinneret. The core liquid is injected into the inner tube of the spinneret. The casting liquid is squeezed into 90% glycerol at 5°C to solidify. The liquid is then washed in an ethylene glycol environment at 50°C and then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane. 3) The hollow fiber membrane is washed with deionized water, then rinsed in a methanol environment at 55°C, and then washed with deionized water and dried to obtain the hollow fiber gas separation membrane. The resulting hollow fiber gas separation membrane has a breaking strength of 69 MPa. The performance of the membrane is tested using a mixture of CO2 and CH4 (volume ratio of 25:75). When the feed gas pressure is 0.12 MPa, the CO2 permeation rate is 1800×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 221.
[0030] Example 4
[0031] A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-K60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C and keeping warm, then adding zirconium oxide powder, ball milling, then adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle and standing for degassing to obtain a membrane casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid. The casting liquid is degassed and then added to a spinneret. The core liquid is injected into the spinneret's inner tube and extruded into 90% glycerol at 5°C to solidify. The casting liquid is then washed in a 50°C ethylene glycol environment and heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane. 3) The hollow fiber membrane is washed with deionized water, rinsed in a 55°C methanol environment, and then rinsed with deionized water and dried to obtain the hollow fiber gas separation membrane. The mass ratio of monoacetin to isobutyl acetate in step 1) is 1:3. The molar ratio of polyethersulfone, sulfonated polyetheretherketone, and polyvinylpyrrolidone-K60 in step 1) is 1:4:2.5. In step 1), the amount of zirconium oxide powder added is 1 / 10 of the mass of polyethersulfone, the rotation speed of the first ball milling is 300 rpm, and the rotation speed of the second ball milling is 550 rpm. The negative pressure state in step 1) is 0.3 atmospheres, the stirring time under the negative pressure state is 6 hours, and the temperature is 30°C. During the static degassing process in step 1), the system is in an ultrasonic oscillation environment, the static degassing time is 4 hours, and the temperature is 30°C. For the obtained hollow fiber gas separation membrane, its breaking strength was detected to be 85 MPa; its performance was tested using a mixed gas of CO2 and CH4 (volume ratio of 30:70). When the feed gas pressure was 0.15 MPa, the CO2 permeation rate was 2800×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 297.
[0032] Example 5
[0033] A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-K60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C and keeping warm, then adding zirconium oxide powder, ball milling, then adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle and standing for degassing to obtain a membrane casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid. The casting liquid is degassed and then added to a spinneret. The core liquid is injected into the spinneret's inner tube and extruded into 90% glycerol at 5°C to solidify. The casting liquid is then washed in a 50°C ethylene glycol environment and heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane. 3) The hollow fiber membrane is washed with deionized water, rinsed in a 55°C methanol environment, and then rinsed with deionized water and dried to obtain the hollow fiber gas separation membrane. The mass ratio of monoacetin to isobutyl acetate in step 1) is 1:3. The molar ratio of polyethersulfone, sulfonated polyetheretherketone, and polyvinylpyrrolidone-K60 in step 1) is 1:4:2.5. In step 1), the amount of zirconium oxide powder added was 1 / 10 of the mass of the polyethersulfone. The initial ball milling speed was 300 rpm, and the secondary ball milling speed was 550 rpm. The negative pressure in step 1) was 0.3 atmospheres, and the stirring period under negative pressure was 6 hours at a temperature of 30°C. During the static degassing process in step 1), the system was subjected to ultrasonic vibrations for 4 hours at a temperature of 30°C. In step 2), the water pressure in the spinning head was 1.8 bar and the water flow rate was 140 mL / min. In step 2), the hollow fiber membrane embryo was in 90% glycerol at 5°C for 50 minutes. The resulting hollow fiber gas separation membrane had a breaking strength of 83 MPa. Performance testing using a mixture of CO2 and CH4 (30:70 by volume) revealed a CO2 permeation rate of 2500 × 10 at a feed gas pressure of 0.13 MPa. -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 312.
[0034] Example 6
[0035] A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-K60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C and keeping warm, then adding zirconium oxide powder, ball milling, then adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle and standing for degassing to obtain a membrane casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid. The casting liquid is degassed and then added to a spinneret. The core liquid is injected into the spinneret's inner tube and extruded into 90% glycerol at 5°C to solidify. The casting liquid is then washed in a 50°C ethylene glycol environment and heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane. 3) The hollow fiber membrane is washed with deionized water, rinsed in a 55°C methanol environment, and then rinsed with deionized water and dried to obtain the hollow fiber gas separation membrane. The mass ratio of monoacetin to isobutyl acetate in step 1) is 1:3. The molar ratio of polyethersulfone, sulfonated polyetheretherketone, and polyvinylpyrrolidone-K60 in step 1) is 1:4:2.5. In step 1), the amount of zirconium oxide powder added was 1 / 10 of the mass of the polyethersulfone. The speed of the initial ball milling was 300 rpm, and the speed of the secondary ball milling was 550 rpm. The negative pressure in step 1) was 0.3 atmospheres, and the stirring period under negative pressure was 6 hours at a temperature of 30°C. During the static degassing process in step 1), the system was subjected to ultrasonic vibration for 4 hours at a temperature of 30°C. In step 2), the water pressure in the spinning head was 1.8 bar, and the water flow rate was 140 mL / min. In step 2), the hollow fiber membrane embryo was in 90% glycerol at 5°C for 50 minutes. The drying in step 3) was vacuum drying at a temperature of 46°C. After the drying step in step 3), the hollow fiber gas separation membrane was maintained in an atmosphere of nitrogen and oxygen in a 1:1 volume ratio for 25 minutes. The fracture strength of the hollow fiber gas separation membrane was 91 MPa. The performance of the membrane was tested with a mixture of CO2 and CH4 (40:60 by volume). When the feed gas pressure was 0.18 MPa, the CO2 permeation rate was 3200×10 - 6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 349.
[0036] The embodiments of the present invention are described in detail above, but the contents are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the scope of the present invention shall be included in the scope of protection of the present invention.
Claims
1. A hollow fiber gas separation membrane, characterized in that: It is prepared by the following method: 1) Add monoacetin and isobutyl acetate to a stirring kettle, stir evenly at 40-60°C, add polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stir at 80-90°C for 1-2h, then cool to 50-60°C, add polyvinyl alcohol, cool to 30-40°C and keep warm, then add zirconium oxide powder, ball mill, then add polyacrylamide, ball mill, stir under negative pressure for 8-12h, transfer to a spinning kettle and let stand for degassing to obtain a casting solution; 2) Diethylene glycol and propylene carbonate are mixed to obtain a core liquid, the casting liquid is degassed and then added to the spinneret, the core liquid is injected into the inner insert of the spinneret, the casting liquid is squeezed into 90% glycerol at 5°C, solidified, then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain hollow fiber membrane fibers; 3) The hollow fiber membrane fibers are cleaned with deionized water, rinsed in a methanol environment at 55° C., and then cleaned with deionized water and dried to obtain the hollow fiber gas separation membrane.
2. A hollow fiber gas separation membrane according to claim 1, characterized in that: In step 1), the mass ratio of monoacetin to isobutyl acetate is 1:2-1:3.
5.
3. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 1), the molar ratio of polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60 is 1:4:2.
5.
4. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 1), the amount of zirconium oxide powder added is 1 / 8 to 1 / 15 of the mass of polyethersulfone, the rotation speed of the first ball milling is 300 rpm, and the rotation speed of the second ball milling is 550 rpm.
5. The hollow fiber gas separation membrane according to claim 1, characterized in that: The negative pressure state in step 1) is 0.2-0.35 atmospheres, the stirring period under the negative pressure state is 5-8 hours, and the temperature is 25-35°C.
6. The hollow fiber gas separation membrane according to claim 1, characterized in that: During the static degassing process in step 1), the system is placed in an ultrasonic oscillation environment, the static degassing time is 3-6 hours, and the temperature is 25-35°C.
7. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 2), the water pressure entering the inner diameter of the spinning head is 1.8 bar and the water flow rate is 140 mL / min.
8. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 2), the hollow fiber membrane embryo is kept in 90% glycerol at 5° C. for no less than 40 minutes.
9. The hollow fiber gas separation membrane according to claim 1, characterized in that: The drying in step 3) is vacuum drying at a temperature of 40-50°C.
10. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 3), after the drying step is completed, the hollow fiber gas separation membrane is kept in a nitrogen and oxygen environment with a volume ratio of 1:1 for 20 to 30 minutes.
Citation Information
Patent Citations
Membranes for separation
CN104010718A
Preparation method of gas separation membrane
CN106422801A